Putative role of prosthetic dental implants in the development of cardiac sarcoidosis: A case-control study - Subramanian, Muthiah; Bera, Debabrata; Theodore, Jospeh; Kishore, Jugal; Srinivas, Akula; Saggu, Daljeet; Yalagudri, Sachin; Narasimhan, Calambur (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Etiopathogenesis of cardiac sarcoidosis is poorly understood. The objective of this study is to examine a putative role of previous dental procedures on the development of cardiac sarcoidosis(CS). Methods: Clinical details of 73 patients with CS from the Granulomatous Myocarditis Registry were analyzed. Data regarding clinical presentation, comorbidities, baseline electrocardiogram, echocardiogram and 18fluorodeoxyglucose(FDG) PET-CT was extracted from the registry database. A comprehensive history of dental procedures for all patients was recorded by the dental surgeon. The two control groups comprised of 79 patients with idiopathic ventricular tachycardia and/or complete heart block(with similar clinical presentation) and 145 healthy age and sex matched patients, respectively. Results: Dental evaluation revealed that patients of CS had undergone a previous prosthetic dental implant (PI,p<0.001) or root canal treatment(RCT,p=0.025) more often than the controls. Among patients with CS, those who had previous dental procedures had higher18FDG uptake, with regards to maximum standardized uptake values(SUV) in the LV myocardium(8·6+3·3vs.5·5 +1·8, p<0·001) and mediastinal lymph nodes(9·3+4·6vs.5·4+1·7, p<0·001) as compared to patients who did not undergo a dental procedure. The subset of CS patients with a previous PI or RCT had higher uptake levels in the myocardium(max SUV 9·4+3·1vs.6·7+2·0,p=0·011,number of abnormal LV Segments 10·3+3·1vs.6·5+2·8,p=0·008) and mediastinal lymph nodes(max SUV 10·5+4·8vs. 7·2+1·8,p=0·002) compared to those who underwent crowning or extraction. In addition,CS was diagnosed after a shorter latency(47·3+21·0vs.81·6+25·3 months<0·001) following PI or RCT compared to crowning or extraction. Conclusions: We observed a significant association between PI and RCT and the occurrence of CS. This group of patients also appear to have a more severe form of the disease.